2019
DOI: 10.3389/fpsyt.2019.00280
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes in Relation to Manic Episode

Abstract: Bipolar disorder (BD) is highly heritable and well known for its recurrent manic and depressive episodes. The present study focused on manic episode in BD patients and aimed to investigate state-specific transcriptome alterations between acute episode and remission, including messenger RNAs (mRNAs), long noncoding RNAs (lncRNAs), and micro-RNAs (miRNAs), using microarray and RNA sequencing (RNA-Seq) platforms. BD patients were enrolled with clinical information, and peripheral blood samples collected at both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…65,[72][73][74] DNA methylation in promoters is typically associated with the repression of gene expression and may underlie at least some of the transcriptomic changes reported for BD in multiple tissues. [75][76][77][78][79] Moreover, several preclinical and clinical studies have shown that early-life traumatic experiences can induce stable methylation alterations that persist into adulthood, suggesting epigenetic-based alterations as mediators of the clinical effects of early adversity. [80][81][82] Interestingly, one of the mechanisms by which methylomes have been shown to interfere with BD phenotype is the modulation of biological aging processes.…”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
“…65,[72][73][74] DNA methylation in promoters is typically associated with the repression of gene expression and may underlie at least some of the transcriptomic changes reported for BD in multiple tissues. [75][76][77][78][79] Moreover, several preclinical and clinical studies have shown that early-life traumatic experiences can induce stable methylation alterations that persist into adulthood, suggesting epigenetic-based alterations as mediators of the clinical effects of early adversity. [80][81][82] Interestingly, one of the mechanisms by which methylomes have been shown to interfere with BD phenotype is the modulation of biological aging processes.…”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
“…In bipolar disorder, biological pathways in relation to PYHIN1 were mainly associated with immune function, especially cytokine–cytokine receptor interaction. 18 PYHIN1 was also regarded as an interferon pathway gene affecting mycobacterium tuberculosis infection and contributed to the induction of interferon response. 10 , 19 The dysregulation of PYHIN1 in pediatric inflammatory bowel disease also suggested the involvement of PYHIN1 in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathway significantly influenced by chronic lithium treatment in our animal mania model was bitter taste receptor pathway. Recent transcriptome study by Lee et al [ 25 ] showed altered taste receptors gene expression during manic episodes. These genes included bitter taste receptors, TAS2R5 and TAS2R3, that were suggested as potential markers specific for the manic state [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent transcriptome study by Lee et al [ 25 ] showed altered taste receptors gene expression during manic episodes. These genes included bitter taste receptors, TAS2R5 and TAS2R3, that were suggested as potential markers specific for the manic state [ 25 ]. These receptors were previously found downregulated (together with olfactory receptors) in the dorsolateral prefrontal cortex of schizophrenia postmortem brain tissues [ 26 ] and this downregulation influenced altered cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation